Effectiveness research on a wavy lamellar plate-type biofilter with a capillary system for the humidification of the packing material applying introinduced microorganisms - Mačaitis, Kęstutis; Misevičius, Antonas; Paškevičius, Algimantas; Raudonienė, Vita; Repečkienė, Jūratė (Journal of Environmental Engineering and Landscape Management, 2014)
To conduct research, a new generation plate-type air treatment biofilter for removing gaseous pollutants from air has been applied under laboratory conditions. A distinguishing feature of the packing material of the biofilter includes wavy lamellar polymer plates placed to each other and producing a capillary effect of humidification. While having such an arrangement, wavy lamellar plates also have rather wide spacing (6 mm), and therefore the employment of the structure of the plate-type packing material decreases the aerodynamic resistance of the device. A wavy porous plate is made of a polymer plate that ensures stiffness. Both sides of the wavy lamellar polymer plate have attached steam exploded birch fiber pellets under which, to increase plate capillarity, not-woven caulking material is put. This technological decision allows effectively enhancing the durability of the biopacking material. The work presents the results of research on the efficiency of the biodestruction process of acetone, xylene and ammonia. With reference to the conducted investigation, the high efficiency of air treatment and microbiological activity has been established. When pollutant gases (acetone, xylene and ammonia), under a velocity of 0.08 m s–1, passed through the biopacking material, microbiological activity in the material reached on average 1×108 cfu/cm2, and air treatment efficiency made 90.7%.